From Existing and New Nuclear and Astrophysical Constraints to Stringent Limits on the Equation of State of Neutron-Rich Dense Matter - Hauke Koehn; Henrik Rose; Peter T. H. Pang; Rahul Somasundaram; Brendan T. Reed; Ingo Tews; Adrian Abac; Oleg Komoltsev; Nina Kunert; Aleksi Kurkela; Michael W. Coughlin; Brian F. Healy; et al. (Physical Review X)
Through continuous progress in nuclear theory and experiment and an increasing number of neutron-star (NS) observations, a multitude of information about the equation of state (EOS) for matter at extreme densities is available. To constrain the EOS across its entire density range, this information needs to be combined consistently. However, the impact and model dependency of individual observations vary. Given their growing number, assessing the various methods is crucial to compare the respective effects on the EOS and discover potential biases. For this purpose, we present a broad compendium of different constraints and apply them individually to a large set of EOS candidates within a Bayesian framework. Specifically, we explore different ways of how chiral effective field theory and perturbative quantum chromodynamics can be used to place a likelihood on EOS candidates. We also investigate the impact of nuclear experimental constraints, as well as different radio and x-ray observations of NS masses and radii. This is augmented by reanalyses of the existing data from binary neutron star coalescences, in particular of GW170817, with improved models for the tidal waveform and kilonova light curves, which we also utilize to construct a tight upper limit of 2.39M_{⊙} on the TOV mass based on GW170817’s remnant. Our diverse set of constraints is eventually combined to obtain stringent limits on NS properties. We organize the combination in a way to distinguish between constraints where the systematic uncertainties are deemed small and those that rely on less conservative assumptions. For the former, we find the radius of the canonical 1.4M_{⊙} neutron star to be R_{1.4}=12.26_{-0.91}^{+0.80}  km and the TOV mass at M_{TOV}=2.25_{-0.22}^{+0.42}M_{⊙} (95% credibility). Including all the presented constraints yields R_{1.4}=12.20_{-0.48}^{+0.50}  km and M_{TOV}=2.30_{-0.20}^{+0.07}M_{⊙}. When comparing these limits to individual data points, we find that the quoted radius of HESS J1731-347 displays noticeable tension with other constraints. Constraining microphysical properties of the EOS proves more challenging. For instance, the symmetry energy slope is restricted to L_{sym}=48_{-25}^{+21}  MeV, where this constraint is mainly dominated by our reanalysis of the PREX-II and CREX experiment.